FINANCIAL LITERACY TRENDS IN THE DIGITAL ECONOMY: A BIBLIOMETRIC STUDY OF COASTAL MSMES IN GORONTALO CITY - Monoarfa, Mohamad Agus Salim; Srie Isnawaty Pakaya (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
This research employs bibliometric tools including PRISMA, VOSviewer, and Publish or Perish (PoP) to systematically analyze 28 peer-reviewed articles from international databases (2020–2025), identifying dominant keywords, thematic clusters, and authorship networks relevant to digital financial literacy. By doing so, it fills a critical gap in understanding the intersection of digital finance, entrepreneurship, and regional economic disparities. The study contributes to the state of the art by offering a contextualized bibliometric roadmap and a synthesis of thematic trends, especially in underexplored rural and coastal economies. Key findings highlight an accelerating trend in digital financial literacy publications post-pandemic, with increased global academic collaboration and focus on financial inclusion, digital entrepreneurship, and fintech adoption. In the Gorontalo context, low digital literacy among coastal MSMEs exacerbated by infrastructure limitations and policy gaps hinders their ability to leverage digital financial tools effectively. The research identifies a strong correlation between local government intervention, tailored digital education, and improved SME sustainability in marginalized regions. This study has substantial implications for evidence-based policymaking, advocating for localized digital literacy initiatives, infrastructure investments, and adaptive regulatory frameworks. The results are expected to guide strategic planning for digital inclusion and enhance the competitiveness of coastal MSMEs in the emerging digital economy.